2005
DOI: 10.2138/am.2005.1960
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron micro-X-ray fluorescence analysis of natural diamonds: First steps in identification of mineral inclusions in situ

Abstract: Diamond inclusions are of particular research interest in mantle petrology and diamond exploration as they provide direct information about the chemical composition of upper and lower mantle and about the petrogenetic sources of diamonds in a given deposit. The objective of the present work is to develop semi-quantitative analytical tools for non-destructive in situ identifi cation and characterization of mineral inclusions in diamonds using synchrotron micro-X-ray Fluorescence (μSXRF) spectroscopy and micro-X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Subsequently, when Rietveld refinement was used to determine quantitative phase analysis of the identified phases, 9 16 the results indicated that the major phase is anhydrite with the addition of calcite, aragonite, halite, quartz, and dolomite phases, see Figure 5 . The findings are supported by the elemental composition (wt %) 37 results obtained from WDXRF spectrometry and Omnian software ( Figure 4 ) for deposits from both reboilers C and D. Therefore, the Rietveld quantitative phase analysis results can guide the engineers at the affected refineries and gas plants to overcome the problems by devising the appropriate corrective procedures. 2 − 5 …”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Subsequently, when Rietveld refinement was used to determine quantitative phase analysis of the identified phases, 9 16 the results indicated that the major phase is anhydrite with the addition of calcite, aragonite, halite, quartz, and dolomite phases, see Figure 5 . The findings are supported by the elemental composition (wt %) 37 results obtained from WDXRF spectrometry and Omnian software ( Figure 4 ) for deposits from both reboilers C and D. Therefore, the Rietveld quantitative phase analysis results can guide the engineers at the affected refineries and gas plants to overcome the problems by devising the appropriate corrective procedures. 2 − 5 …”
Section: Resultssupporting
confidence: 55%
“…In contrast, the filtrated deposits from reboiler B showed the presence of different irregularly shaped microscopic particles ( Figures 2 and 3 ). The element concentration (wt %) 37 obtained from high-resolution PANalytical Advanced AXIOS WDXRF spectrometry and the instrument’s standardless software (i.e., Omnian) revealed that the major elements are Ca and S and the minor elements are Cl, Sr, Si, Mg, Fe, Mn, and Na ( Figure 4 ). The Ca element is formed from water.…”
Section: Resultsmentioning
confidence: 99%
“…31 SR-GIXRF, unlike SR-μXRF, a bulk analysis method, depends on the quality of the surface of the material. 26 Kawai et al., using a combination of TXRF/XPS and assisted by an X-ray synchrotron beam, reported the angle dependence of photoelectron peak intensity for a system of bilayers tungsten–silicon (W/Si) on an Si wafer. 32 SR-GIXRF was already used in qualitative determination of hybrid nanomaterials in our research group.…”
Section: Introductionmentioning
confidence: 99%
“…25 If a conventional X-ray source (such as the X-ray tube) is used for this purpose, the collimation would result in an X-ray flow too low to be useful in XRF experiments. 26 Our research group earlier published the SR-mXRF mapping of phosphotungstates ([PW 12 O 40 ] 3À ) in the characterization of hybrid nanomaterials. 27,28 In grazing angle X-ray fluorescence (GIXRF), the X-ray incident beam is almost parallel to surface of the sample at angles equal or slightly larger (two to three times) than the value of the critical angle of sample's support.…”
Section: Introductionmentioning
confidence: 99%
“…The reported absolute uncertainties in the Ca contents of Ca-silicate minerals were AE5-6 wt%. So, this technique appears to be more useful for mineral identification rather than for full chemical analysis (Sitepu et al, 2005). More recently, Yasuzuka et al (2009) proposed a method to estimate the Mg# value [¼ 100ÁMg mol /(Mg þ Fe) mol ] of olivine inclusions from their Raman spectra with an uncertainty of AE0.8.…”
Section: Introductionmentioning
confidence: 99%